Passionate about early childhood educational policy, practice, and pedagogy: exploring intersections between discourses, experiences, and feelings...knitting new terms of belonging - Whitty, Pam; Lysack, Monica; Lirette, Patricia; Lehrer, Joanne; Hewes, Jane (My University, 2020)
We are five early childhood researchers, from across Canada, thrown together amongst a series of alarming discourses, where developmental, economic, and neuroscientific rationales for ECEC drown out alternative theoretical perspectives, as well as personal experience, values, subjective knowledges, and the fierce passion we feel for our work. In the midst of this "throwntogethness" (Massey, 2005), how do we bring our situated knowings and desires to these discursive material relational mashups? How do we engage with the throwntogetherness that is the Canadian ECEC field as we knit together alternative ways of being, doing, and acting, figuring out what resonates in localized situations (Osgood, 2006)? To begin to answer these questions, we think with feminist theory (Bezanson; 2018; Langford et al., 2016; Prentice, 2009); the politics of the event of place, (Massey, 2005) and relational and spatial networked discursive entanglements (Massey, 2005; Nichols et al., 2012; Ingold, 1995; Haraway, 2016) as we untangle three vignettes related to advocating for a competent universal public ECEC system; writing post-developmental curriculum frameworks; and weaving productive relationships between university researchers and early childhood practitioners. These vignettes illuminate our struggles to "stay with the trouble," as Haraway (2016) suggests, stubbornly hanging on to the hope of producing new terms of belonging (Burns & Lundh, 2011) as a form of resistance, allowing us to open up spaces to imagine, tell alternative stories (Moss, 2014), and create real change within our local contexts.
Keywords: early childhood education; policy; curriculum; relationships; feminist theory; throwntogetherness